2014
DOI: 10.1172/jci69735
|View full text |Cite
|
Sign up to set email alerts
|

Aging and epigenetic drift: a vicious cycle

Abstract: The term epigenetics refers to stable patterns of gene expression that are seen during differentiation or X chromosome inactivation and are not dependent on dynamic changes in coding DNA. These gene expression states are encoded in the epigenome -a collection of marks on DNA or on histone tails that are established during embryogenesis. Genome-wide studies in aging cells and tissues have uncovered stochastic DNA methylation drift (gradual increases or decreases at specific loci) that reflects imperfect mainten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

22
296
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 345 publications
(326 citation statements)
references
References 82 publications
22
296
0
2
Order By: Relevance
“…Recent studies targeting the whole genome demonstrated overall hypomethylation in association with aging as well as increased methylation in specific promoter CGIs. [26][27][28] In this study, we also observed decreased methylation in older patients. However, the methylation difference between "younger" and "older" AML patients was less prominent than the difference between cytogenetic risk groups.…”
Section: Discussionsupporting
confidence: 78%
“…Recent studies targeting the whole genome demonstrated overall hypomethylation in association with aging as well as increased methylation in specific promoter CGIs. [26][27][28] In this study, we also observed decreased methylation in older patients. However, the methylation difference between "younger" and "older" AML patients was less prominent than the difference between cytogenetic risk groups.…”
Section: Discussionsupporting
confidence: 78%
“…1 Studies of aging and genetic dysregulation (e.g., cancer) support a decrease in global genomic DNA methylation (hypomethylation) concurrent with locus-specific increases in DNA methylation (hypermethylation). 2,3 Consequently, epigenetic drift has emerged as a biomarker for aging, with increased DNA methylation targeting developmental genes. 1,4 The preponderance of evidence to date, however, has been measured in crosssectional samples, thereby lacking a longitudinal component of evaluating DNA methylation changes in paired samples over time.…”
Section: Introductionmentioning
confidence: 99%
“…This phenomenon is highly reminiscent of previously reported patterns of DNA methylation associated with aging and cancer (Issa, 2014). Specifically, methylation drift occurs during aging and cancer development, with numerous studies identifying an increase in site-specific DNA methylation (e.g.…”
Section: Resultssupporting
confidence: 55%